2023
DOI: 10.1002/uog.24907
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection is improved by watertightness of fetal spina bifida repair in the sheep model

Abstract: Objectives A contributing factor to unsuccessful prenatal spina bifida aperta (SBA) repair via an open approach may be incomplete neurosurgical repair causing persistent in-utero leakage of cerebrospinal fluid (CSF) and exposure of the fetal spinal cord to amniotic fluid. We aimed to investigate the neurostructural and neurofunctional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…We also evaluated the white matter in our fetal surgery population, and, again, no differences in volume or shape were found compared to normal controls [ 26 ]. These fetuses however had a variable degree of ventriculomegaly prior to fetal surgery; after the operation, the ventricular width continued to increase, in concordance with the observations of others [ 8 12 16 26 ]. To us, it remains unclear how the white matter volume evolves during the remainder of the pregnancy and in postnatal life in this subset of patients.…”
Section: Fetal Brain Mri In Spina Bifida Apertasupporting
confidence: 89%
See 1 more Smart Citation
“…We also evaluated the white matter in our fetal surgery population, and, again, no differences in volume or shape were found compared to normal controls [ 26 ]. These fetuses however had a variable degree of ventriculomegaly prior to fetal surgery; after the operation, the ventricular width continued to increase, in concordance with the observations of others [ 8 12 16 26 ]. To us, it remains unclear how the white matter volume evolves during the remainder of the pregnancy and in postnatal life in this subset of patients.…”
Section: Fetal Brain Mri In Spina Bifida Apertasupporting
confidence: 89%
“…Earlier studies, such as the one from Sutton [ 11 ]), also reported such changes between three and six weeks after the surgery in all fetuses where this was measured. The re-accumulation of intracranial CSF can be an interesting proxy of the efficacy of spinal closure [ 12 ].…”
Section: Fetal Brain Mri In Spina Bifida Apertamentioning
confidence: 99%
“…This technique is used clinically for fetoscopic repair with the purpose of arresting CSF leakage. 14,32,33 The multi-layered closure included dural coverage with dural patch followed by skin approximation but without myofascial or paraspinal muscle closure-which is not possible in this model. The experiment was not designed to compare different neurosurgical techniques but to determine the difference in local host response to different dural patches.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded animals that displayed any signs of insufficient or non-watertight closure as unsuccessful closure may be less neuroprotective. 14 The experiment was neither powered to study the spectrum of effects of incomplete SBA closure. Data from incomplete closure were not considered for analysis as experiments in large animal models demonstrate that ongoing leakage is associated with deterioration of hindlimb motor function, hence it is likely to be less neuroprotective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation